COVID-19 Vaccination in Patients With Multiple Sclerosis on Disease-Modifying Therapy. Issue 4 (August 2021) - Wolf, Andrew; Alvarez, Enrique
Abstract : The COVID-19 pandemic has resulted in challenges for the practice of neurology. One major concern is how to best manage patients with multiple sclerosis (MS) who are on disease-modifying therapies (DMTs). DMTs frequently have immunosuppressive properties that both increase the risk for COVID-19 and potentially reduce the immunologic response to vaccination in a group already vulnerable to infection due to neurologic deficits. Here, we review early data on COVID-19 outcomes in patients with MS and discuss what is known about vaccine effectiveness in those on anti-CD20 and sphingosine-1-phosphate receptor agents, which are proposed to have attenuating effects based on their mechanisms of action. In addition, we provide recommendations to best use novel COVID-19 vaccines in this population and highlight what information may better inform vaccine strategies in the future.